PENERAPAN DIGITAL MARKETING SEBAGAI STRATEGI PEMASARAN UNTUK MENINGKTKAN PENDAPATAN BUMDES TUNAS MANDIRI DALAM ERA SOCIETY 5.0 - Daulani, Ahmad; Yuliana, Yuliana; Resky, Kartika; Lisapaly, David CE; Breemer, Yacob (Insanta : Jurnal Pengabdian Kepada Masyarakat, 2024)
To optimize the income achieved by BUMDes Tunas Mandiri Wawouru village, it is very necessary to use digital marketing. The aim of carrying out this PKM activity is so that BUMDes Tunas Mandiri ministrators and MSMEs are able to understand and recognize the use of digital marketing as a marketing strategy to increase BUMDes Tunas Mandiri's income in the Era of Society 5.0. The method used in this activity is the lecture and discussion method. The results of implementing this PKM activity showed a positive response in receiving material during the activity and showed high interest as indicated by the evaluation results, each of which showed very significant changes. The first indicator shows an achievement percentage of 80%, the second indicator shows an achievement percentage of 70%, the third indicator shows an achievement percentage of 85%. So that by holding PkM activities with the theme Digital Marketing to Increase the Income of BUMDes Tunas Mandiri in the Society 5.0 Era, it can be followed up and used as a sustainable promotional media to increase the income of BUMDes Tunas Mandiri in Wawouru village, Palangga sub-district, South Konawe district, Southeast Sulawesi province.